The Effectivity of Mind Mapping as Preparation Media for Selection of Advanced Studies to Higher Education - Taty Fauzi; Valeri Adventa Tiffany Nathani Ela (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2022)
Mind mapping is a way to record obtained information by mapping the mind which done creatively to make it more effective and easier to absorb by the brain. The purpose of this study is to determine the effectiveness of mind mapping media as a preparation for choosing a study to higher education. Current research is a quantitative pre-experimental research with a one group pre-test post-test design. The mind mapping used is a syllabus, a type of mind mapping that can provide an overview of what students know and learn. Media "Mind Map" consists of several dimensions, the concept is adjusted to the mind set of each. Students make plans for career choices according to the direction of their talents, interests and personalities. The research population was class of XI students at UPT SMA Negeri 8 Banyuasin. Sampling was done purposively. The sample of this study was 31 students. Data collected was analysed using paired sample T-Test. The results showed that the mind mapping media was significantly effective used as a preparation techniques for the selection of college studies by students of SMA Negeri 8 Banyuasin. This shows that mind mapping is can be used by BK teachers/school counselors as a media in providing services to prepare for the selection of further studies to college.